Avaliação do potencial efeito antiinflamatório da pioglitazona (agonista de pparg) e do fenofibrato (agonista de ppara) em diferentes modelos experimentais "in vivo" - Antonio Carlos Pinheiro de Oliveira (2005)
Peroxisome proliferator activated receptors (PPAR) are ligand-regulated transcription factors that control the expression of many genes by interacting directly with specific DNA sequences. The agonists of these receptors were originally approved for the treatment of type 2 diabetes mellitus and dislipidemia. Many studies have demonstrated that PPAR agonists, in addition to their effects on carbohydrate and lipid metabolism, present some antiinflammatory properties. However, many of these studies have been carried out in vitro and the effects of these drugs in experimental models of nociception, edema, fever e granulomahave not been fully investigated. Thus, the objective of the present study was to evaluate the effect of pioglitazone (PPARg agonist) and fenofibrate (PPARa agonist) on experimental models of nociception, edema, fever and granuloma, in order to obtain a wider knowledge of the potential anti-inflammatory effect of these drugs. Acute treatment with pioglitazone (50 or 100 mg/kg, i.p.) or acute and prolonged treatment with fenofibrate (100 or 300 mg/kg, p.o.) did not inhibit the nociceptive response induced by heat in the hot plate model in mice. Similarly, pioglitazone and fenofibrate did not inhibit the first phase of formaldehyde-inducednociceptive response in mice. However, the second phase of this response was inhibited by treatment with pioglitazone (5 or 25 mg/kg, i.p.) or fenofibrate (100 or 300 mg/kg.day, seven days). Acute treatment with pioglitazone (10 or 50 mg/kg, i.p.) or fenofibrate (100 or 300 mg/kg, p.o.) also did not inhibit mechanical allodynia induced by carrageenan in rats.However, the initial phase of this response was inhibited by the prolonged treatment with fenofibrate (100 ou 300 mg/kg.day, seven days). Acute treatment with pioglitazone (10, 25 or 50 mg/kg, i.p.) and the acute (100 or 300 mg/kg, p.o.) or prolonged treatment (100 or 300 mg/kg.day, seven days) with fenofibrate inhibited the paw edema induced by carrageenan in rats. Although pioglitazone and fenofibrate inhibited the edema and allodynia induced by carrageenan, the effects induced by PDD, a protein kinase C activator, were not very expressive. Mechanical allodynia induced by PDD in rats was not inhibited by any of theagonists. However, paw edema induced by carrageenan was partially reduced by treatment with pioglitazone (50 mg/kg, i.p.). In the investigation of the effects of these drugs in a model of a systemic manifestation of inflammation, the febrile response induced by LPS in rats, itwas observed that acute or prolonged treatment with fenofibrate (100 or 300 mg/kg, p.o.) did not induce an antipyretic effect. On the other hand, acute treatment with pioglitazone (10 or 50 mg/kg, i.p.) augmented the magnitude of febrile response induced by LPS and increasedthe colonic temperature per se. Prolonged treatment with pioglitazone (10 or 25 mg/kg.day, i.p., seven days) or fenofibrate (100 or 300 mg/kg.day, p.o., seven days) did not inhibit the granuloma induced by the subcutaneous implant of cotton in rats. In conclusion, the resultsdemonstrate that pioglitazone and fenofibrate, agonist of PPARg and PPARa, respectively, present antinociceptive and antiedematogenic activity in different experimental models. These results represent the first demonstration of the antinociceptive and antiedematogenic activitiesof fenofibrate and pioglitazone and give further support to the potential use of these PPAR agonists in the treatment of different inflammatory diseases.